Effects of Abelmoschus manihot (L.) and its combination with irbesartan in the treatment of diabetic nephropathy via the gut–kidney axis - Yu, Hongmei; Tang, Haitao; Saxu, Rengui; Song, Yuhui; Cui, Xu; Xu, Jingjing; Li, Nan; Cui, Siyuan; Ge, Haitao; Tang, Wei; Gu, Harvest F. (Frontiers in Pharmacology, 2024)
Background Clinical observations have recently shown that Abelmoschus manihot (L.) in the form of Huangkui capsule (HKC) and in combination with irbesartan (EB) is an effective therapy for diabetic nephropathy (DN) in patients with type 2 diabetes (T2D). The present study aims to explore the mechanisms underlying the therapeutic efficacies of HKC and its combination with EB in DN via the gut-kidney axis. Methods HKC, EB, and their combination or vehicle were administered in db/db mice, which is an animal model for the study of T2D and DN. Comparative analyses of the gut microbiota, serum metabolites, and kidney transcriptomics before and after drug administration were performed. Results After treatment with HKC, EB, and their combination for 4 weeks, the urinary albumin-to-creatinine ratios decreased significantly in the db/db mice with DN. In terms of the gut microbiota, the abundances of Faecalitalea, Blautia, and Streptococcus increased but those of Bacteroidetes, Firmicutes, Enterobacteriaceae, and Desulfovibrio decreased. Parallelly, serum metabolites, mainly including quercetin 3′-glucuronide and L-dopa, were elevated while cortisol and cytochalasin B were reduced. Furthermore, the S100a8, S100a9, Trem1, and Mmp7 genes in the kidneys were downregulated. These altered elements were associated with proteinuria/albuminuria reduction. However, EB had no effects on the changes in blood pressure and specific differentially expressed genes in the kidneys. Conclusion The present study provides experimental evidence that HKC regulates the gut microbiota, circulating metabolites, and renal gene activities, which are useful for better understanding of the action mechanisms of A. manihot in the treatment of DN through the gut-kidney axis.